Vet as an Education Pathway and the School to Work Transition for Bulgaria’s Rural Youth - Milenkova, Valentina; Nakova-Manolova, Albena; Lendzhova, Vladislava (Calitatea Vieții, 2023)
This paper focuses on vocational education as a catalyst for the entry of young people from rural areas into the labour market. The analysis presents an assessment of the state of professional training from the point of view of the quality of graduatesʼ practical training and its compliance with the requirements of the labour market. The study presents the perspectives of three types of social entities relevant to entering the labour market – vocational schools, businesses and local government. The purpose of the paper is to highlight the specific features of the assessments and opinions of the various actors in a substantive plan and to present the possibilities generated by professional education, such as creating a link between the supply and demand of skills. The smooth transition from education to employment of young people from rural regions is required to lower the percentage of NEETs in rural settings and to generate a better rural environment.